2023
DOI: 10.1177/10690727231163321
|View full text |Cite
|
Sign up to set email alerts
|

Decent Work, Posttraumatic Stress Disorder, and Posttraumatic Growth From the Psychology of Working Perspective: A Three-Wave Study of Military Personnel

Abstract: Scholarly interest in the relationship between decent work and mental health based on the Psychology of Working Theory has recently increased. This study evaluated the indirect effects of survival, social contribution, and self-determination needs satisfaction on the relationship between decent work and trauma-related mental health among military personnel. We conducted a three-wave survey over 1 year. Results showed that decent work predicted satisfaction of the three basic needs. Additionally, survival needs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 92 publications
1
7
0
Order By: Relevance
“…In Autin et al (2019), only social contribution and self-determination needs predicted job satisfaction, which is identical to the current study as survival need satisfaction was a nonsignificant predictor of work fulfillment. Finally, in Seol et al (2023), the three needs predicted PTSD and post traumatic growth. First, considering the similarities, it may be that meeting survival needs through one's job has less of a connection with how one feels about that job and more of a connection with overall mental and physical health.…”
Section: Overall Model Findingsmentioning
confidence: 95%
See 4 more Smart Citations
“…In Autin et al (2019), only social contribution and self-determination needs predicted job satisfaction, which is identical to the current study as survival need satisfaction was a nonsignificant predictor of work fulfillment. Finally, in Seol et al (2023), the three needs predicted PTSD and post traumatic growth. First, considering the similarities, it may be that meeting survival needs through one's job has less of a connection with how one feels about that job and more of a connection with overall mental and physical health.…”
Section: Overall Model Findingsmentioning
confidence: 95%
“…Recent studies also have demonstrated support for PWT's posited outcomes of decent work. Studies have consistently demonstrated across a variety of samples that decent work attainment is linked to meeting the three work-related needs proposed within PWT (survival, social contribution, and self-determination; Duffy et al, 2019Duffy et al, , 2021Kim et al, 2021;Seol et al, 2023). Other studies have focused on the links between decent work and more distal work outcomes, such as job satisfaction, meaningful work, turnover intentions, and mental and physical health.…”
Section: Psychology Of Working Theorymentioning
confidence: 99%
See 3 more Smart Citations